Multicriteria approach to select the most economically advantageous tender: The application of AHP in Italian public procurement. Issue 3 (1st August 2019) - Marcarelli, Gabriella; Nappi, Andrea
Abstract : Purpose: This paper aims to show how the proposed approach (two analytic hierarchy process [AHP] models) may allow dealing with the best tender selection process in an organic and simple way and ensure the consistency check of the judgements, the necessary step for having reliable results. At first, this paper highlights some critical issues regarding the weighted sum model (WSM) and the algorithms frequently used to evaluate the most economic advantageous tender. Then, it proposes to extend the AHP approach to the evaluation of both the qualitative and quantitative components of a public procurement award. Finally, the WSM and the AHP are applied to the same case study to show, step by step, some criticisms of the former and some advantages of the latter. Design/methodology/approach: This paper proposes to apply two AHP models to evaluate both qualitative and quantitative components of a public tender. The quality and cost models allow to identify and select the tender associated with the highest quality/cost ratio. Findings: The assessment of the WSM and the AHP models, and some differences between them, build upon their application as an example of public procurement. A case study is used as a teaching device (Yin, 2003 ) to highlight why the AHP may provide different results. In particular, an important issue concerning the evaluation of qualitative requirements is explored: the consistency of judgements expressed by the committee members. Social implications: This approach provides analytical tools for public management that allow appropriate implementation of their management function and allow a realisation of the strategic objectives of European Union law and Italian legislation on public procurement. It would help managers to prioritise their goals and criteria and evaluate them in a scientific way. The model integrates multiple qualitative and quantitative criteria, simplifies the selection process, achieves optimal use of funds and leads to cost savings. It allows to reduce the discretional power of both the contracting issuer, in the choice of the formula to adopt for calculating the coefficients, and the committee members, allowing tender evaluation to have more trust and ensure the fairness of public procurement matters and quality of the object purchased. Originality/value: This paper proposes the use of two hierarchical models to evaluate qualitative and quantitative requirements and provide the ranking among several tenders.